A preliminary study on Malaysian polytechnics students’ academic credentials and its relationship to education choice on TVET - Foo, Jyy Wei; Jamil, Hazri; Abd Razak, Nordin (Politeknik Sultan Abdul Halim Mu'adzam Shah, 2016)
The purpose of this paper is to provide information and in depth comprehension related to the research findings on the education choice on TVET among Malaysian polytechnics’ students in terms of program enrolled and its academic credentials. The academic credentials studied consist of two variables which are the availability of the desired program and employment opportunities. There are 47 students from a Malaysian polytechnic were participated in this study. The study employed a self administered questionnaire measuring the mentioned variables. Descriptive test and rank biserial correlation were conducted on the data analysis. Results suggest that there is a weak association between the education choice in terms of program enrolled and academic credentials in terms of the availability of desired program among Malaysian polytechnics’ students. On the other hand, the results also suggest that there is no association between the education choice in term of program enrolled and academic credentials in terms of employment opportunities. Future research suggested to be carried out is on exploring the other academic credentials’ variables on education choice on TVET among Malaysian polytechnics students.